Kecerdasan emosional sebagai salah satu faktor penentu keputusan pembelian - Wahid , Nisa Noor; Marino , Wilman San; Fadillah , Adil Ridlo (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The rapid development of technology has led to the rise of marketplaces, one of which is Shopee. This study aims to examine purchasing decisions of shopee, which are influenced by promotional factors, shopping safety, consumer trust, and emotional intelligence. The money research method is the quantitative method using primary data sourced from 280 students of the Faculty of Economics and Business, Siliwangi University, who are users of the shopee application. The results obtained are simultaneously promotions, consumer trust, shopping safety, and emotional intelligence influence purchasing decisions at the shopee marketplace in Tasikmalaya City. Partially, purchasing decisions at Shopee are positively and significantly influenced by promotions, consumer trust, and shopping safety, while emotional intelligence has a significant negatif effect. It was found that emotional intelligence had a negatif effect and promotions, and promotions, consumer trust, and shopping safety positively affected purchasing decisions, indicating that purchases made by students at Tasikmlaaya through shopee were carried out rationally.